Treatment of rubber glove wastewater by ultrafiltration - Yap, P.S.; Ibrahim, Shaliza; Ang, K.B. (Faculty of Science, University of Malaya, 2013)
The feasibility of using flat-sheet ultrafiltration polyethersulfone (PES) membranes for treatment of effluent from a rubber glove factory has been investigated. Membranes of molecular weight cut-off (MWCO) 100 kDa and 10 kDa were operated in cross-flow filtration to evaluate the efficiency of rejections of certain selected parameters in the wastewater. The membrane operation was carried out at a condition of 1.0 bar for the inlet pressure and 0.2 bar for the outlet pressure. The parameters tested were chemical oxygen demand (COD), total suspended solids (TSS), ammoniacal nitrogen (AN), total Kjeldahl nitrogen (TKN), turbidity, pH, colour and trace metals. In addition, COD tests were also carried out for dead-end filtration of filter paper for comparison. The overall best results came from cross-flow filtration of 10 kDa membranes, where high percentage of rejection was recorded for COD (73.07%), TSS (90.61%) and turbidity (96.60%). The results also showed that the permeate produced can be safely discharged into watercourses in compliance with the legal requirements of Malaysia’s environmental laws and regulations. (Keywords: Flat sheet PES membranes, MWCO 100 kDa and 10 kDa, ultrafiltration, rubber glove wastewater)